Simultaneous ground-based and in situ Swarm observations of equatorial F-region irregularities over Jicamarca - S. Aol; S. Buchert; E. Jurua; M. Milla (Annales Geophysicae, 2020)
Ionospheric irregularities are a common phenomenon in the low-latitude ionosphere. They can be seen in situ as depletions of plasma density, radar plasma plumes, or ionogram spread F by ionosondes. In this paper, we compared simultaneous observations of plasma plumes by the Jicamarca Unattended Long-term Investigations of the Ionosphere and Atmosphere (JULIA) radar, ionogram spread F generated from ionosonde observations installed at the Jicamarca Radio Observatory (JRO), and irregularities observed in situ by Swarm in order to determine whether Swarm in situ observations can be used as indicators of the presence of plasma plumes and spread F on the ground. The study covered the years from 2014 to 2018, as this was the period for which JULIA, Swarm, and ionosonde data sets were available. Overall, the results showed that Swarm's in situ density fluctuations on magnetic flux tubes passing over (or near) the JRO may be used as indicators of plasma plumes and spread F over (or near) the observatory. For Swarm and the ground-based observations, a classification procedure was conducted based on the presence or absence of ionospheric irregularities. There was a strong consensus between ground-based observations of ionospheric irregularities and Swarm's depth of disturbance of electron density for most passes. Cases, where ionospheric irregularities were observed on the ground with no apparent variation in the in situ electron density or vice versa, suggest that irregularities may either be localized horizontally or restricted to particular height intervals. The results also showed that the Swarm and ground-based observations of ionospheric irregularities had similar local time statistical trends with the highest occurrence obtained between 20:00 and 22:00 LT. Moreover, similar seasonal patterns of the occurrence of in situ and ground-based ionospheric irregularities were observed with the highest percentage occurrence at the December solstice and the equinoxes and low occurrence at the June solstice. The observed seasonal pattern was explained in terms of the pre-reversal enhancement (PRE) of the vertical plasma drift. Initial findings from this research indicate that fluctuations in the in situ density observed meridionally along magnetic field lines passing through the JRO can be used as an indication of the existence of well-developed plasma plumes.